RECENT DEVELOPMENTS IN THE FINTECH INDUSTRY - THOMAS J. CHEMMANUR; MICHAEL B. IMERMAN; HARSHIT RAJAIYA; QIANQIAN YU (Journal of Financial Management, Markets and Institutions, 2020)
In this article, we review some recent developments in the field of Financial Technology or “FinTech.” We begin with an overview of what FinTech is and why it has become an important growth industry in the financial services area and therefore an important research topic in finance. In the next section, we review some of the academic literature in the FinTech area. In the subsequent section, we characterize the financing of FinTech startups, especially by venture capital firms. In the following section, we characterize innovation by FinTech firms as well as by incumbent financial intermediaries. In the next section, we move on to discuss potential sources of value creation by FinTech start-up firms relative to existing incumbent firms: we conjecture that one source of value creation may arise from FinTech startups being able to provide a superior customer experience relative to incumbent firms in various areas of consumer finance. In the following section, we discuss the regulatory environment facing FinTech firms, in their banking as well as in their financial market activities. In the penultimate section, we analyze the buy-versus-build decision facing firms choosing to enter the FinTech sector and discuss the trade-offs that may drive such decisions in practice. We conclude with some remarks about the future directions that may be taken by the FinTech industry.